1994
DOI: 10.1200/jco.1994.12.6.1272
|View full text |Cite
|
Sign up to set email alerts
|

Unknown primary carcinoma: natural history and prognostic factors in 657 consecutive patients.

Abstract: This study validated previously identified important prognostic factors for survival in UPC. Additional variables that had an impact on survival were identified and the complex interaction of the factors was explored. As patient numbers increase, this database will be able to provide further analyses of patient subsets and potentially relate specific clinical features to the evolving molecular and biochemical understanding of these malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
153
3
29

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 319 publications
(202 citation statements)
references
References 22 publications
12
153
3
29
Order By: Relevance
“…Considering the influence of gender, Abbruzesse et al (1994) found that women lived longer, while Snyder et al (1979) found no difference in survival between men and women. Our finding that survival time is shorter in patients with more metastases is a common finding in UPT patients (Abbruzzese et al, 1994). The influence of therapy is nil in several studies Greco and Hainsworth, 1993); in our study, patients receiving any kind of therapy lived longer, although it should be remarked that the number was small (n 5 9) and that they were not treated according to one standard protocol.…”
Section: Survival Analysis In Upt Patientscontrasting
confidence: 47%
See 3 more Smart Citations
“…Considering the influence of gender, Abbruzesse et al (1994) found that women lived longer, while Snyder et al (1979) found no difference in survival between men and women. Our finding that survival time is shorter in patients with more metastases is a common finding in UPT patients (Abbruzzese et al, 1994). The influence of therapy is nil in several studies Greco and Hainsworth, 1993); in our study, patients receiving any kind of therapy lived longer, although it should be remarked that the number was small (n 5 9) and that they were not treated according to one standard protocol.…”
Section: Survival Analysis In Upt Patientscontrasting
confidence: 47%
“…However, we should bear in mind that these results are based on a relatively small number of patients. Earlier studies did not find any influence of age on survival of UPT patients either (Snyder et al, 1979;Abbruzzese et al, 1994). Considering the influence of gender, Abbruzesse et al (1994) found that women lived longer, while Snyder et al (1979) found no difference in survival between men and women.…”
Section: Survival Analysis In Upt Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…These lengths and rates of survival are similar to those observed for patients with chemotherapy-treated metastatic lung, pancreatic, and gastric carcinomas, among others. 7 In a review of Ͼ600 patients with CUP who were evaluated for treatment at The University of Texas M. D. Anderson Cancer Center (M. D. Anderson; a tertiary referral center) from 1987 to 1992, 8 the median survival was 11 months, 90% of patients received anticancer treatment, and 49.2% of patients received chemotherapy.…”
mentioning
confidence: 99%